VALIDATION OF HPLC AND UV VISIBLE METHODS FOR FEW SELECTED BLOOD PRESSURE LOWERING DRUGS AND THEIR FORMULATIONS - M, Shahul Hameed; K, Jat R; N, Indulatha V (Universal Journal of Pharmaceutical Research, 2017)
Objective: A simple, precise and accurate RP-HPLC method has been developed and subsequently validated for simultaneous estimation of Aliskiren Hemifumarate and Nicardipine Besylate from their combination dosage form. Aliskiren and Nicardipine are widely used antihypertensive drugs at present but their analytical methods are very costly and very complex to simplify the methods with increasing sensitivity new methods were developed which are simple, precise, eco-friendly, less time consuming, rapid and fast and economically chief. Methods: First standard curve was plotted then the method is validated by using recovery studies, linearity, correctness and reproducibility, robustness, ruggedness, detection limit, quantification limits, stability studies etc. The validated technique has been with success used for stress testing analysis of Aliskiren and Nicardipine. Results: The stress testing studies revealed that the tactic was with success utilized to resolve the degraded product from the sample. From the peak purity profile it had been demonstrated that there was no interference of degradation product and the purity of angle were found to be but the purity of threshold. This work was undertaken with an aim of developing HPLC and Specrophotometric techniques for analysis of Aliskiren and Nicardipine. Number of trials was taken for selection of column and M. Phase’. The proposed method was validated as per the ICH and USP guidelines. Conclusion: The stress testing studies revealed that the tactic was with success utilized to resolve the degraded product from the sample. From the peak purity profile it had been demonstrated that there was no interference of degradation product and the purity of angle were found to be but the purity of threshold. Peer Review History: Received 9 December 2016; Revised 11 January 2017; Accepted 13 February, Available online 15 March 2017 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Mohamed Salama , Modern University for Technology & Information, Egypt, salama47@yahoo.com Dr. Mohammad Shaheen Khan , University Malaysia Sabah, Malaysia, shaheenchem@gmail.com